The Effect of Employee Competence and Leadership on Organizational Performance With Work Culture as A Moderating Variable in Efiyanto Trading Business - Zega, Mesriana Yustina; Elazhari; Zsazsa, Cut Sah Kha Mei (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
This study aims to examine the influence of employee competence and leadership on organizational performance at Efiyanto Trading Company, with work culture as a moderating variable. The research method used was quantitative, with a sample size of 40 people. Primary data collection techniques included observation, interviews, and questionnaires, and were tested using validity and reliability tests. This quantitative research method employed path analysis. The results showed that employee competence and leadership had a positive and significant effect on organizational performance. Work culture moderated the relationship between employee competence, leadership, and organizational performance. Employee competence contributed 49.6% to performance, while leadership contributed 52.9%. Simultaneously, employee competence, leadership, and work culture explained 69.2% of the variance in organizational performance. This study recommends improving employee competence through training, enhancing leadership quality through emotional intelligence development, and strengthening a positive work culture at Efiyanto Company to sustainably improve organizational performance.